Commentary—How Necessary Is the Right of Assembly? - Robert K. Vischer (Washington University Law Review, 2012)
As a political culture seemingly hard-wired for the full-throated championing of individual rights, we are not quite sure what to do with liberty claims by groups. Whether we are talking about corporate speech rights, the treatment of religious student groups at public universities, the limits of the ministerial exception, the Boy Scouts‘ right to discriminate, or churches‘ access to public schools, we have seen a recent spate of conflicts involving groups that have spawned both political battles and landmark Supreme Court rulings. As such, our uneasiness with the right of association as a constitutional matter may have something to do with our uneasiness with the freedom of association as a political matter. We do not quite know what to do with groups. Judging from the public reaction to the Court‘s Citizens United ruling, we do know that Americans tend to reject the notion that the corporate person possesses rights on par with the natural person. And while citizens are more inclined to defend the autonomy of religious groups, it is not clear whether that inclination is just a relatively weak extension of our traditionally strong commitment to individual religious liberty, or whether there is meaningful recognition of the importance of group liberty. Especially outside the context of religious organizations, the deference owed to groups by the surrounding political community remains unsettled.
Keywords: & quot; Liberty& #x27; s Refuge: The Forgotten Freedom of Assembly& quot; John Inazu; Freedom of assembly; Right to exclude; Group rights